3rd European Evidence-based Consensus on the Diagnosis and Management of Crohn’s Disease 2016: Part 1: Diagnosis and Medical Management - Gomollón, Fernando; Dignass, Axel; Annese, Vito; Tilg, Herbert; Van Assche, Gert; Lindsay, James O.; Peyrin-Biroulet, Laurent; Cullen, Garret J.; Daperno, Marco; Kucharzik, Torsten; Rieder, Florian; Almer, Sven; et al. (Journal of Crohn's and colitis, 2017)
This paper is the first in a series of two publications relating to the European Crohn's and Colitis Organisation [ECCO] evidence-based consensus on the diagnosis and management of Crohn's disease and concerns the methodology of the consensus process, and the classification, diagnosis and medical management of active and quiescent Crohn's disease. Surgical management as well as special situations including management of perianal Crohn's disease of this ECCO Consensus are covered in a subsequent second paper [Gionchetti et al JCC 2016].